2020
DOI: 10.34133/2020/4370817
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of Dynamic Silver Crystallization Driven by Chemical Reaction and Diffusion

Abstract: Rational synthesis of materials is a long-term challenging issue due to the poor understanding on the formation mechanism of material structure and the limited capability in controlling nanoscale crystallization. The emergent in situ electron microscope provides an insight to this issue. By employing an in situ scanning electron microscope, silver crystallization is investigated in real time, in which a reversible crystallization is observed. To disclose this reversible crystallization, the radicals ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In experiments on chemical systems, previous research has led to stationary Turing patterns occurred in the chlorite-iodide-malonic acid [5][6][7] (CIMA) and the Belousov-Zhabotinsky 8,9 (BZ) reactions. Later, a number of two-and three-dimensional Turing structures was investigated in chemical 10,11 and living systems 12,13 . Very recently, Tan and co-workers reported the preparation of a Turing-type polyamide membrane, which shows markedly enhanced watersalt separation performance compared to the conventional desalination membranes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In experiments on chemical systems, previous research has led to stationary Turing patterns occurred in the chlorite-iodide-malonic acid [5][6][7] (CIMA) and the Belousov-Zhabotinsky 8,9 (BZ) reactions. Later, a number of two-and three-dimensional Turing structures was investigated in chemical 10,11 and living systems 12,13 . Very recently, Tan and co-workers reported the preparation of a Turing-type polyamide membrane, which shows markedly enhanced watersalt separation performance compared to the conventional desalination membranes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…316 Calculated results indicated that the concentrations of radicals generated from the irradiation were spatiotemporally variable in the liquid cell due to the diffusion and reaction of radicals. 316 The fluctuation of the reductive hydrated electrons and the oxidative hydroxyl radicals in the cell leads to the alternative dominance of the reduction and oxidation reactions. The reduction leads to the growth of Ag crystals while the oxidation leads to their dissolution, resulting in the reversible Ag crystallization.…”
Section: Npsmentioning
confidence: 99%
“…The fluctuation of the reductive hydrated electrons and the oxidative hydroxyl radicals in the cell leads to the alternative dominance of the reduction and oxidation reactions. The reduction leads to the growth of Ag crystals while the oxidation leads to their dissolution, resulting in the reversible Ag crystallization …”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the chemical diffusion and reaction regulate the chemical distribution around the growth front of particles, which influences the structure evolution of materials, which provides a green and powerful technique for the rational synthesis of materials. In this study, inspired by the reaction–diffusion regulation device, we successfully synthesized a-MoS x catalysts with diverse morphologies in ambient conditions by the electrodeposition method and further discovered their shape-dependent property for electrocatalytic hydrodesulfurization. Among them, the MoS x nanoparticles exhibit the highest hydrodesulfurization efficiency of thiophene, reaching 22.5%.…”
Section: Introductionmentioning
confidence: 99%